Exploring the Decision-Making Process of Pre-Service Teachers in Solving Mathematics Literacy Problems - Murtafiah, Wasilatul; Lukitasari, Marheny; Lestari, Nurcholif Diah Sri (Mathematics Education Journal, 2021)
Students’ lack of mathematical literacy skills is also accompanied by the lack of mathematical literacy skills of most pre-service teachers. The purpose of this study is to investigate the decision-making process conducted by pre-service teachers in solving mathematical literacy problems. This qualitative descriptive study involved two subjects taken from 42 pre-service mathematics teacher students. Each subject was identified based on their pattern in solving mathematical literacy problems correctly and inappropriately. Data were collected through tests of mathematical literacy problems and test-based interviews. The results showed that there were differences in the decision-making process done by the students with correct and incorrect problem solving, namely: (1) building ideas, having three vs. two solution ideas, formulating and employing correctly vs. formulating correctly and employing inappropriately; (2) clarifying ideas, giving reasons for each idea vs. having wrong reasons due to calculation errors, interpreting correctly vs. interpreting incorrectly; and (3) assessing the reasonableness of an idea, providing logical reasons with one choice vs. logical reasons with one choice but less sure. Based on the findings, it can be concluded that the creativity of prospective teacher students in building ideas is still low and reasoning in expressing and choosing ideas is still weak, causing immature decision making. The finding of this study provides suggestions for educators to provide structured assignments and for other researchers to find factors influencing pre-service teachers’ decision-making in mathematics problem-solving to improve pre-service teachers’ decision-making skills. DOI: https://doi.org/10.22342/jpm.15.2.13908.145-160